The impacts of the development process from the rural communities’s perspectives: Sultan Abu Bakar Dam / Idrees Mohammed Taha Abdullah Young - Mohammed Taha Abdullah Young, Idrees (2021)
Land development by the government or any private company without a doubt is beneficial for a certain target group of people, to ease them with their daily life. However, a small percentage of people would be negatively affected by the development especially when it involves losing their land, homes, culture and being unable to voice their opinion. Disturbance to native community, implication on the native land ownership and erosion of value and respect for land is one of the problems has been faced by native on Sultan Abu Bakar Dam area. The aim of this research is to study the effects of the development process on rural and native communities. To identify issues on the rural native land development, to determine effect of development process on native land and to suggest improving strategy overcoming negative effect. Quantitative method has been chosen to carry out the study. The targeted population respondents for this research are focus on to the randomly questionnaire from Google Form it is more relevant so that all the natives understand the meaning of the question and will assist them to answer the questionnaire. The findings, there are several issues on the rural native land development which is the most natives agree is the development should have chosen another area for the dam, the native needed contact with others through the development and development has helped the natives with their basic life necessities such as clean water access to the mainland and the last one.